Development and Evaluation of the OF Pelvis Score for Osteoporotic Pelvic Ring Fractures – A Retrospective Assessment of Therapy Recommendations for 107 Patients - Spiegl, Ulrich Josef Albert; Schnake, Klaus J.; Scheyerer, Max J; Mendel, Thomas; Osterhoff, Georg; Sprengel, Kai; Bäumlein, Martin; Behr, Lars; Franck, Alexander; Gercek, Erol; Grüninger, Sebastian; Hartung, Philipp; Hauck, Stefan; Jacobs, Cornelius; Katscher, Sebastian; Klauke, Friederike; Liepold, Katja; Müller, Christian W.; Müller, Michael; Piltz, Stefan; Pätzold, Robert; Riehle, Marion; Schmeiser, Gregor; Verheyden, Akhil P.; Zimmermann, Volker; Ullrich, Bernhard (Zeitschrift für Orthopädie und Unfallchirurgie, 2024)
The aim of this study was to develop a simple and reliable score which supports decision making between non-operative and operative treatment in patients with osteoporotic pelvic fractures.Between 2018 to 2020, the OF Pelvis Score was developed during a total of 5 meetings of the Working Group on Osteoporotic Fractures of the Spine Section of the German Society of Orthopaedics and Trauma. The OF Pelvis Score as a decision aid between non-surgical and surgical treatment was developed by expert consensus after analysis of numerous geriatric sacral and pelvic ring fractures from several hospitals. Subsequently, retrospective evaluation of the score was performed on consecutive patients from three hospitals.The following parameters were considered relevant to decision making between non-surgical and surgical treatment and were incorporated into the score: fracture morphology using the OF Pelvis Classification, pain status, level of mobilisation, fracture-related neurological deficits, health status, and the modifiers already integrated into the OF Pelvis classification. If the score is < 8, non-surgical therapy is recommended; if the score is > 8, surgical therapy is recommended; if the score is 8, there is a relative indication for surgery. The OF Pelvis Score was then evaluated retrospectively in a total of 107 patients, according to records. The OF Pelvis Score was 8 points in 4 patients (3.7%), all of whom received surgical treatment. Of the remaining 103 patients, 93 received score-compliant therapy (90.3%). Among these, 4 of the patients who did not receive score-compliant care refused the recommended surgery, so the actual therapy recommendation was score-compliant in 94.2%.The OF Pelvis Score can be used to derive a therapy recommendation in many patients in clinical practice. Because of the possible change of clinical parameters during the course of the disease, the score has a dynamic character. In the retrospective evaluation, the recommendations from the OF Pelvis Score were in close accordance with the therapy actually performed.Ziel dieser Studie war die Entwicklung und klinische Evaluation eines Scores, der bei der Entscheidung für eine konservative oder operative Therapie bei osteoporotischen Beckenfrakturen unterstützen soll.In den Jahren 2018 bis 2020 erfolgte die Entwicklung des OF-Pelvis-Scores im Rahmen von insgesamt 5 Treffen der AG Osteoporotische Frakturen der Sektion Wirbelsäule der DGOU. Der OF-Pelvis-Score als Entscheidungshilfe zwischen konservativer und operativer Therapie wurde im Expertenkonsens nach Analyse zahlreicher geriatrischer Sakrum- und Beckenringfrakturen aus mehreren Kliniken entwickelt. Anschließend erfolgte die retrospektive Evaluation des Scores an konsekutiven Patienten aus 3 Kliniken.Folgende Parameter wurden für die Entscheidung zwischen operativem und konservativem Vorgehen als relevant angesehen und flossen in den Score ein: Frakturmorphologie anhand der OF-Pelvis-Klassifikation, Schmerzsituation, Mobilisation, frakturbedingte neurologische Defizite, Gesundheitszustand sowie die Modifier, die bereits in die OF-Pelvis-Klassifikation integriert sind. Bei einem Punktwert < 8 wird eine konservative Therapie empfohlen, bei einem Punktwert > 8 eine operative und bei einem Punktwert von 8 besteht eine relative Operationsindikation. Der OF-Pelvis-Score wurde dann bei insgesamt 107 Patienten retrospektiv nach Aktenlage berechnet. Der OF-Pelvis-Score betrug 8 Punkte bei 4 Patienten (3,7%), die alle operativ versorgt wurden. Von den restlichen 103 Patienten wurden 93 Score-konform therapiert (90,3%). Dabei lehnten 4 der nicht Score-konform versorgten Patienten die empfohlene Operation ab, sodass die tatsächliche Therapieempfehlung in 94,2% Score-konform war.Der OF-Pelvis-Score basiert auf der Frakturmorphologie und klinischen Parametern und ermöglicht die Ableitung einer Therapieempfehlung. Aufgrund der verwendeten klinischen Parameter ist der Score dynamisch und spiegelt die sich ändernde klinische Situation auch im Verlauf wider. In der retrospektiven Evaluation zeigten die OF-Pelvis-Score-basierten Therapieempfehlungen eine sehr hohe Übereinstimmungsrate mit der tatsächlich durchgeführten Therapie.
Keywords: osteoporotic pelvic fractures; classification; non-operative treatment; surgical treatment; decision-making